The effect of modelling the way strategy on students' writing procedure text ability at the eleventh grade of MAS Al-Abraar Siondop Julu in 2020/2021 academic year - amelia rahmadani lubis (JURNAL LINER (Language Intelligence and Educational Research), 2021)
ABSTRACT: The result of this research: 1) The application of modelling the way strategy on students can be seen from 16 aspects observed by the observer the total score was 48 and the average was 3 it was “Good” categorized. It mean that the writer using modelling the way strategy on writing procedure text is well, 2) The students writing procedure text before and after using modelling the way strategy. It can be seen from the students’ frequency before using modelling the way strategy was on 44.09 or 10 students, it was categories “Fail” and after using modelling the way strategy was 69.13 or 9 students, these were categories “Enough”, 3) There is any significant effect of modelling the way strategy on students writing procedure text ability. Normality test shows that sig value 0.039>0.05 pretest and posttest 0.027>0.05. Homogeneity Test shows that the value of (Sig.) of the pretest 0.346>0.05 it means that the sample variances is homogenuous. Pair sample ttest that significant value was less than 0.05 (0.000<0.05). So, Ha is accepted. It means that there is any significant of using modelling the way strategy on students writing procedure text ability at the eleventh grade of MAS Al-Abraar Siondop Julu. Keywords: Modelling the Way, Strategy, Writing, Procedure Text ABSTRAK: Hasil penelitian ini: 1) Penerapan strategi modeling the way pada siswa dilihat dari 16 aspek yang diamati oleh pengamat diperoleh total skor 48 dan rata-rata 3 berkategori “Baik”. Artinya penulis menggunakan strategi modeling the way dalam menulis teks prosedur dengan baik, 2) Siswa menulis teks prosedur sebelum dan sesudah menggunakan strategi modeling the way. Hal ini dapat dilihat dari frekuensi siswa sebelum menggunakan pemodelan strategi jalan pada 44,09 atau 10 siswa termasuk kategori “Gagal” dan setelah menggunakan pemodelan strategi jalan adalah 69,13 atau 9 siswa, ini adalah kategori “Cukup”, 3) Ada pengaruh yang signifikan strategi modeling the way terhadap kemampuan teks prosedur menulis siswa. Uji normalitas menunjukkan nilai sig 0,039> 0,05 pretest dan posttest 0,027> 0,05. Uji Homogenitas menunjukkan nilai (Sig.) Dari pretest 0,346> 0,05 artinya varians sampel homogen. Pair sample ttest yang memiliki nilai signifikan lebih kecil dari 0,05 (0,000 <0,05). Jadi, Ha diterima. Artinya ada pengaruh penggunaan strategi modeling the way terhadap kemampuan teks prosedur menulis siswa kelas XI MAS Al-Abraar Siondop Julu. Kata Kunci: Modelling the Way, Strategy, Writing, Procedure Text